2003
DOI: 10.1021/bi035227w
|View full text |Cite
|
Sign up to set email alerts
|

RPE65 Operates in the Vertebrate Visual Cycle by Stereospecifically Binding All-trans-Retinyl Esters

Abstract: RPE65 is a major protein of unknown function found associated with the retinyl pigment epithelial (RPE) membranes [Hamel, C. P., Tsilou, E., Pfeffer, B. A., Hooks, J. J., Detrick, B., and Redmond, T. M. (1993) J. Biol. Chem. 268, 15751-15757; Bavik, C. O., Levy, F., Hellman, U., Wernstedt, C., and Eriksson, U. (1993) J. Biol. Chem. 268, 20540-20546]. RPE65 knockouts fail to synthesize 11-cis-retinal, the chromophore of rhodopsin, and accumulate all-trans-retinyl esters in the RPE. Previous studies have also sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 33 publications
3
67
0
Order By: Relevance
“…We did not observe any effect of all-trans-retinol addition on the localization of LRAT, which remained ER-associated. Of note is that the T-REx-293 cells we used for these experiments do not express detectable levels of RPE65, a protein proposed in some studies to be a retinyl ester-binding/transport protein (42,43), yet we were still able to detect retinosome formation. The N Terminus of LRAT Is Not Conserved in All VertebratesAnalysis of the N-terminal domains of the known and putative vertebrate homologs of LRAT showed a low degree of conservation.…”
Section: The Putative C-terminal Transmembrane Domain Is Necessary Fomentioning
confidence: 80%
See 2 more Smart Citations
“…We did not observe any effect of all-trans-retinol addition on the localization of LRAT, which remained ER-associated. Of note is that the T-REx-293 cells we used for these experiments do not express detectable levels of RPE65, a protein proposed in some studies to be a retinyl ester-binding/transport protein (42,43), yet we were still able to detect retinosome formation. The N Terminus of LRAT Is Not Conserved in All VertebratesAnalysis of the N-terminal domains of the known and putative vertebrate homologs of LRAT showed a low degree of conservation.…”
Section: The Putative C-terminal Transmembrane Domain Is Necessary Fomentioning
confidence: 80%
“…The RPE65 protein is currently the only protein known to associate with retinyl esters (42,43). It has been reported that RPE65 is involved in the isomerization reaction that produces 11-cis-retinol and that retinyl esters are the preferred substrates for this reaction (51)(52)(53).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The accumulation of retinyl esters is clearly dependent on LRAT activity (Figure 2), and these esters accumulate in Rpe65−/− mice. RPE65 was also proposed to be a retinyl esterbinding protein (27,44,45), hinting of its possible role in this process. Most insightful was the observation made by Pepperberg et al that, in normal RPE, there is a substantial exchange of all-trans-retinol with the blood circulation, whereas in Rpe65−/−mice, despite the presence of abnormally high molar levels of RPE retinyl esters, the outward movement is inhibited (43).…”
Section: Accumulation Of All-trans-retinyl Esters In the Rpementioning
confidence: 99%
“…This is partly because the putative IMH (3), or alternate isomerase (5), has yet to be identified at the molecular level, and partly due to uncertainties in understanding the mechanism of isomerization (5,17,18). The precise role of RPE65 in isomerization has been particularly perplexing, although its absolute necessity is demonstrated by the Rpe65-deficient mouse (14).…”
mentioning
confidence: 99%